Carbon isotopic composition of dissolved inorganic carbon (δ13C-DIC) at IODP Site 370-C0023, Nankai Trough subduction zone - Köster, Male; Liu, Bo; Ijiri, Akira; Spivack, Arthur J; Morono, Yuki; Inagaki, F; Heuer, Verena B; Kasten, Sabine; Henkel, Susann (PANGAEA, 2025)
This dataset includes the carbon isotopic composition of dissolved inorganic carbon (δ13C-DIC) of sediment cores that were retrieved from Site C0023 (Hole A) during International Ocean Discovery Program (IODP) Expedition 370 in the Nankai Trough offshore Japan in the Pacific Ocean (Drilling vessel Chikyu). Site C0023 was established on 17 September 2016. Coring terminated on 3 November 2016.